3D printing and solar cell fabrication methods: A review of challenges, opportunities, and future prospects - Bonsa Regassa Hunde; Abraham Debebe Woldeyohannes (Results in Optics, 2023)
In the solar cell industry, three-dimensional (3D) printing technology is currently being tested in an effort to address the various problems related to the fabrication of solar cells. 3D printing has the ability to achieve coating uniformity across large areas, excellent material utilization with little waste, and the flexibility to incorporate roll-to-roll (R2R) and sheet-to-sheet (S2S) systems. The main aim of this review is to highlight the key gaps in current solar cell manufacturing processes and to point out the use of 3D printing technology as an alternative in solar cell fabrication. The present paper provides a comprehensive review of solar cell fabrication methods, with a focus on 3D printing technology applications in solar cell fabrication. Drawbacks with the conventional solar cell manufacturing systems, solar cell development challenges, and future prospects are also highlighted. The paper concludes that 3D printing technology can be a viable candidate to fabricate solution-processable solar cells over a wide area with excellent material utilization and good flexibility. The study might lead to more research and investigations into 3D printing technologies' applications in the solar cell industry.